Dispositivos desencadenantes de estrés y ansiedad en estudiantes de odontología de la Universidad de Antioquia (2008)
ABSTRACT: This study recognized those devices generating stress and anxiety originated during the educational practices of dental students. Methods: qualitative study which used different methods of gathering information such as Zung’s Test, which allows to measure stress or anxiety levels; the non structured interview and the reconstruction of life stories. Results: parting from these, the most important triggering devices of stress or anxiety were revealed, and they were: excessive academic load, working to please the instructor, and fear of accidents of biological risks. Conclusions: it was possible to recognize these devices in two daily surroundings of their educational processes: the academic and occupational interactions associated with physical manifestations such as tension, fatigue or pain, fear, anguish, concern, aggressiveness, indifference, and lack of concentration, among others.